Conditional citizens : on belonging in America - Lalami, Laila, 1968- (Pantheon Books, 2020)
"The acclaimed, award-winning novelist--author of The Moor's Account and The Other Americans--now gives us a bracingly personal work of nonfiction that is concerned with the experiences of "conditional citizens." What does it mean to be American? In this starkly illuminating and impassioned book, Pulitzer Prize Finalist Laila Lalami recounts her unlikely journey from Moroccan immigrant to U.S. citizen, using it as a starting point for her exploration of the rights, liberties, and protections that are traditionally associated with American citizenship. Tapping into history, politics, and literature, she elucidates how accidents of birth--such as national origin, race, or gender--that once determined the boundaries of Americanness still cast their shadows today. Throughout the book, she poignantly illustrates how white supremacy survives through adaptation and legislation, with the result that a caste system is maintained, keeping the modern equivalent of white male landowners at the top of the social hierarchy. Conditional citizens, she argues, are all the people whom America embraces with one arm, and pushes away with the other. Brilliantly argued and deeply personal, Conditional Citizens weaves together the author's own experiences with explorations of the place of nonwhites in the broader American culture"--